SHORT REVIEW OF DIFFERENT MICROFLORA FROM THE ORAL CAVITY OF SNAKES - GHOSH, TANMAY; BISWAS, M. K.; ROY, PRADIPTA; GUIN, CHIRANJIB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Snakebites are an enormous public health concern in tropical and subtropical countries. Along with poisoning it also yields some secondary infections in victims. There are many pathogenic microflora in snake’s oral cavity. Snakes typically live in the rhizosphere where various bacterial strains exist and they can lead to opportunistic human diseases. A short review has been done to record different types of microflora isolated from the oral cavity and surface of various snakes. The obtained findings demonstrated significant bacterial pathogens in oral cavity of venomous and non-venomous snakes. Therefore, not only anti-venom treatment but also, due the probability of infections, the diagnosis and treatment should be considered in victims.